Awareness level of north-west zone of Nigeria retail customers towards Islamic banking - Usman Dalhatu, D.B. (American Scientific Publishers, 2015)
Nigeria is a country with a large population of Muslims, where Islamic banking is at infancy stage with just one newly introduced Islamic Bank, that is, Jaiz Bank Plc. However, given the current extensive program of financial reforms in Nigeria and the rapid growth of Islamic banking in comparable economics, there is growing pressure for a system of Islamic banking to be developed. There is then a pressing need for research into the prospects of Islamic banking from a customer perspective in Nigeria through creating awareness. The main objective of this study is to assess people of North-western Nigeriansâ level of awareness toward Islamic banking that is from the retail customerâs perspective. Survey research design was conducted on the retail customersâ level of awareness toward Islamic banking in order to achieve this objective. Descriptive statistics, Independent sample t-test and one way ANOVA was used to analyze the data. The findings of this study will be of key importance to future researchers in the field of Islamic banking, financial industry and financial policy formations in Nigeria. Â© 2015 American Scientific Publishers. All rights reserved.